The Impact of the Auditing Efficiency of the Certified Public Accountants in Bangkok Metropolitan Region - Rungjaturong, Suwannee (Mahachula Academic Journal, 2023)
This research has three objectives as follows: (1) to study the impact of the Code of Conduct on the knowledge and efficiency of the auditor's audit work in the Bangkok Metropolitan Region. (2) to study the impact of experience on the auditor’s knowledge and performance of the Certified Public Accountants in Bangkok Metropolitan Region. (3) To study the impact of knowledge on the auditor's audit work performance in Bangkok Metropolitan Region. In addition, there was a sample group of 312 auditors in Bangkok Metropolitan Region. The instruments used in the study were questionnaires and statistics used in data analysis, consisting of mean, standard deviation, and multiple regression analysis. The results of the research found that Certified Public Accountant's Experience Knowledge and Capability of Certified Public Accountant Affects the audit learning technical performance of duties Relationship and communication the organizational skills were statistically significant at 0.01 and 0.05 levels.